Estudo da sinterização de cavacos de aço ferritico - Menezes, Roberto Cavalcante de (2012)
This research studies the sintering of ferritic steel chips from the machining process. Were sintered metal powder obtained from machining process chips for face milling of a ferritic steel. The chip was produced by machining and characterized by SEM and EDS, and underwent a process of high energy mill powder characterized also by SEM and EDS. Were constructed three types of matrixes for uniaxial compression (relation l / d greater than 2.5). The differences in the design of the matrixes were essentially in the direction of load application, which for cylindrical case axial direction, while for the rectangular arrays, the longer side. Two samples were compressed with different geometries, a cylindrical and rectangular with the same compaction pressure of 700 MPa. The samples were sintered in a vacuum resistive furnace, heating rate 20 °C / min., isotherm 1300 °C for 60 minutes, and cooling rate of 25 °C / min to room temperature. The starting material of the rectangular sample was further annealed up to temperature of 800 ° C for 30 min. Sintered samples were characterized by scanning electron microscopy, optical microscopy and EDS. The sample compressed in the cylindrical matrix did not show a regular density reflecting in the sintered microstructure revealed by the irregular geometry of the pores, characterizing that the sintering was not complete, reaching only the second phase. As for the specimen compacted in the rectangular array, the analysis performed by scanning electron microscopy, optical microscopy and EDS indicate a good densification, and homogeneous microstructure in their full extent. Additionally, the EDS analyzes indicate no significant changes in chemical composition in the process steps. Therefore, it is concluded that recycling of chips, from the processed ferritic steel is feasible by the powder metallurgy. It makes possible rationalize raw material and energy by manufacture of known properties components from chips generated by the machining process, being benefits to the environment